Pendampingan Pemasaran Bisnis Katering Ibu-ibu PKK melalui Pemanfaatan Digital Marketing melaui Aplikasi WhatsApp Business di Dusun Petiyin Solokuro Lamongan - Ishaq, Zamroni; Muhyidin, Muhyidin; Rosida, Eva Alifatur; Mufattikhatin, Mufattikhatin; Wimantara, Ikhwansyah Nata; Afandi, Syahrir (Opportunity Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This activity started from the need for the PKK women's group, Petiyin hamlet, Takerharjo village, Solokuro sub-district, Lamongan district to develop catering activities into a business unit, the problem is that so far the PKK women's group has not carried out marketing activities in introducing their products, especially digital marketing activities. amidst today's technological sophistication, PKK women must be able to market their products online using digital marketing. One of the applications used is WhatsApp Business. Through socialization and training on digital marketing strategies by utilizing social media, it is hoped that the PKK women's group will be able to provide knowledge about how to expand consumer networks in marketing their products so that they can increase their competitive advantage. To achieve this, the Insud KKN Team provided outreach and training to PKK women to plan and create a business, create promotions, use the WhatsApp business application and provide assistance to complete the equipment needed for cooking activities.